2017
DOI: 10.1177/0271678x17738701
|View full text |Cite
|
Sign up to set email alerts
|

A combination antioxidant therapy to inhibit NOX2 and activate Nrf2 decreases secondary brain damage and improves functional recovery after traumatic brain injury

Abstract: Uncontrolled oxidative stress contributes to the secondary neuronal death that promotes long-term neurological dysfunction following traumatic brain injury (TBI). Surprisingly, both NADPH oxidase 2 (NOX2) that increases and transcription factor Nrf2 that decreases reactive oxygen species (ROS) are induced after TBI. As the post-injury functional outcome depends on the balance of these opposing molecular pathways, we evaluated the effect of TBI on the motor and cognitive deficits and cortical contusion volume i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 68 publications
1
58
0
Order By: Relevance
“…5) and -Syn −/− mice (Fig. 8), all 3-to 4-month-old males, were subjected to the MWM test to examine poststroke spatial learning and memory capabilities (32). The test consists of eight blocks of testing over 4 days, followed by a probe trial.…”
Section: Mwm Testmentioning
confidence: 99%
“…5) and -Syn −/− mice (Fig. 8), all 3-to 4-month-old males, were subjected to the MWM test to examine poststroke spatial learning and memory capabilities (32). The test consists of eight blocks of testing over 4 days, followed by a probe trial.…”
Section: Mwm Testmentioning
confidence: 99%
“…Furthermore, studies on cognitive deficits in non-vascular disease demonstrated that increased NOX2 and p47phox expression and activation was involved in cognitive impairment in traumatic brain injury (TBI) [ 116 , 117 , 118 , 119 ], various encephalopathies [ 120 , 121 , 122 , 123 ], and metabolic diseases [ 13 , 124 , 125 ]. Chandran at al.…”
Section: Association Of Nadph Oxidase In Cognitive Impairmentmentioning
confidence: 99%
“…Chandran at al. [ 116 ] reported that NOX2 increased and transcription factor Nrf2 that decreased ROS were induced after TBI. The combination therapy (NOX inhibitor apocynin + Nrf2 activator TBHQ) improved cognitive dysfunction in TBI [ 116 ].…”
Section: Association Of Nadph Oxidase In Cognitive Impairmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuclear factor erythroid 2‐related factor 2, a classical cytoprotective transcription factor, has been reported to impart protective effects against oxidative injury . Nrf‐2 is combined with its inhibitor Keap‐1 as a heterodimer in the cytoplasm under normal conditions .…”
Section: Introductionmentioning
confidence: 99%